THE NOTION OF HAPPINESS IN LATGALIAN FAIRY TALES - Juško-Štekele, Angelika (Via Latgalica, 2008)
Happiness as an ethical category and as one of the most universal dimensions of human world views has been recognized as one of the most important concepts in the specification of ethnic culture within the paradigm of humanitities. The objective of this paper is therefore to reveal the notion of happiness in Latgalian fairy tales. For this purpose, one hundred Latgalian fairy tales were selected in which the word ‘happiness’ was used in different forms and combinations. Taking into consideration the specifics of a folklore text, a linguoculturological approach was used to determine the notion of happiness in Latgalian folklore, and to observe the concept of happiness in folklore texts in the discourses of language and culture and of language and ethnic mentality (Маслова 2001: 28). This concept is interpreted in this paper as a body of collective knowledge, which expresses itself through language and which shows the specifics of an ethnic culture (Воркачев 2002: 22). Three components are distinguished in the structure of the concept – a notional, a figurative, and an axiological component. Of these, the notional component is considered to be the most important one by the majority of researchers (Карасик 1999: 39). It is disclosed in the semantics of the language of folklore when studying the lexemes that happiness is connected with, in the analysis of semantic and pragmatic aspects of the word ‘happiness’, regarding word combinations where happiness is described specifically along the most typical components, and from a contrastive view which allows to identify happiness in comparison to unhappiness. Contextual semantics of the notion of happiness reveals one of the most common theories of the notion of happiness – happiness as luck or as a coincidence of favorable circumstances. A lucky situation can in Latgalian fairy tales also be defined according to the importance of the task which has to be accomplished by a hero and when it is particularly difficult or even impossible to fulfil. In such cases, happiness is denoted with the use of adjectives and as an accomplishment, thereby changing the emphasis from chance to the lucky hero. In the end of the fairy tales, the adverb ‘laimeigi’ (‘happily’) or the adjective ‘laimeigs/-a’ (‘happy’) appears most often in combination with the word ‘dzeivuoja’ (‘lived’), thereby suggesting that there is a special awareness of the word combination „happy life” in Latgalian consciousness. Final formulas of fairy tales relating to the basic elements of happiness distinguish social well-being from the well-being of a family. In addition, fragments of other values contribute to elements of happiness in the final formulas, for example, life/health, harmony, and even loneliness. Under the influence of Christianity, wealth looses importance as a subject of happiness, and its place is taken by the combination of poverty and happiness. A perspective of action of the characters regarding happiness in fairy tales is also created by verbs, which allow to divide characters into three groups: those who look for happiness for themselves, those who give happiness to others, and those who try to deprive others of happiness. Traditionally, protagonists of fairy tales fall into the first group. Their actions are described by using the verbs ‘to look for’, ‘to get’, ‘to meet’, ‘to catch’, or ‘to inquire’, which all imply an active behaviour. In the second group there are so called magic helpers, whose actions are characterized by the verbs ‘to wish’, ‘to make’, ‘to give’, ‘to promise’, or ‘to enchant’. In the third group there are the antagonists of a hero who are best described with the word ‘to envy’. Verbs as a characterization of an attitude towards happiness attest an active position of the characters in the Latgalian fairy tales. Even when happiness is predetermined, the characters do not remain static but actively participate in securing happiness. According to the logic of mythological thinking, happiness is made understandable and organized in recognizable artistic images and positioned in the local environment in equivalence to humans. Two of the most popular artistic techniques of substantiating happiness are anthropomorphization and objectification, which evolve along demythologization. There are two ways of interpreting happiness as an anthropomorphic image. First, the characterization of happiness emphasizes elements symbolizing prosperity and wealth: happiness is dressed in gold and silver (12.A.735.), it appears as a corpulent woman (11.A.735.) or a beautiful girl whose wreath shines like the sun (7.), etc. The second technique is to describe the appearance of happiness in correspondence to the hero’s psychological notion of happiness – when a hero is unhappy, happiness is a black old maid (7.), pale or exhausted (15.A.735.567.). Typical of a hero’s attitude towards happiness are persistence and even superiority. Additional features in the anthropomorphic image of happiness are revealed in those fairy tales where happiness tries its strength against the personifications of other moral values, such as wisdom (8.A.736.). In the end of these fairy tales, wisdom has to admit that wisdom without happiness is not possible. Equally great significance of both moral values (also in reversed priority) is revealed in the paroemiac folk foundation: Laima bez gudreibas ir caurojs maiss. (LSD, 1940 2971) (Happiness without wisdom is like a sack full of holes). An objectification of happiness appears in fairy tales where the idea of happiness is immanently part of the idea of money as a source and a content of happiness. In these fairy tales money can appear to people in the form of a wolf, a bird, a midge, etc. Such an interpretation of happiness was probably determined by the human belief in happiness and the possibility of finding it. Happiness can appear in different unexpected ways, and humans shall only be prepared to recognize it and grasp it. The analyzed material of fairy tales shows how the Latgalians see, understand and evaluate happiness. To sum up the conclusions made in the paper, it shall be noted that happiness is one of the highest moral values of the Latgalians. It is interpreted as both luck and destiny. The Latgalians are active regarding happiness – they look for happiness and they find it. If necessary, they remind happiness of their existence and are not afraid of changing their lives. Regarding the content of values of happiness, the most important parts are well-being (different ways of wealth/prosperity) and family happiness (with a spouse or parents). However, under the influence of Christianity, fairy tales introduced also philosophical contemplation about the problem – whether happiness really is about wealth, whether a poor person can be happy, and whether happiness is possible in this world at all. Folklore does not give the one and only correct answer to what happiness is. Folklore shows where happiness could possibly be and how one can obtain it. Specific aspects of the interpretation of happiness in Latgalian folklore can also be found in other genres of folklore, for instance in folk songs and brahilogisms. It is very well possible that other ethnic groups emphasize different aspects in the interpretation of happiness which should be studied separately. However, as studies of the concept of happiness point out, due to the influence of globalization ethnic differences in the interpretation of happiness could be evened out (Veenhoven 1995: 5).